PET Imaging of Bacterial Infections with Fluorine‐18‐Labeled Maltohexaose1. (21st October 2014) - Ning, Xinghai; Seo, Wonewoo; Lee, Seungjun; Takemiya, Kiyoko; Rafi, Mohammad; Feng, Xuli; Weiss, Daiana; Wang, Xiaojian; Williams, Larry; Camp, Vernon M.; Eugene, Malveaux; Taylor, W. Robert; et al.
Abstract A positron emission tomography (PET) tracer composed of 18F‐labeled maltohexaose (MH18F) can image bacteria in vivo with a sensitivity and specificity that are orders of magnitude higher than those of fluorodeoxyglucose (18FDG). MH18F can detect early‐stage infections composed of as few as 105E. coli colony‐forming units (CFUs), and can identify drug resistance in bacteria in vivo. MH18F has the potential to improve the diagnosis of bacterial infections given its unique combination of high specificity and sensitivity for bacteria.